Explicit Model Predictive Control via Nonlinear Piecewise Approximations*. Issue 18 (2016) - Trinh, Van-Vuong; Alamir, Mazen; Bonnay, Patrick; Bonne, François
Abstract: In this paper, a novel identification methodology is proposed to capture general multivariate nonlinear relationships, with focus on the bounded-error approximation of model predictive control for constrained (non)linear systems. The formulation of the identification problem takes, at each iteration, the form of a constrained linear (or quadratic) optimization problem that is mathematically feasible as well as numerically tractable. The efficiency of the proposed method for the derivation of low-complexity explicit model predictive controllers is demonstrated via the constrained control of a thermodynamic power plant.